Cervical Versus Thoracolumbar Spinal Deformities: A Comparison of Baseline Quality-of-Life Burden. Issue 10 (December 2018) - Passias, Peter G.; Poorman, Gregory W.; Lafage, Virginie; Smith, Justin; Ames, Christopher; Schwab, Frank; Shaffrey, Chris; Segreto, Frank A.; Horn, Samantha R.; Bortz, Cole A.; Varlotta, Christopher G.; Hockley, Aaron; et al.
Abstract : Study Design: Retrospective analysis of 2 prospectively collected multicenter databases, one for cervical deformity (CD) and the other for general adult spinal deformity. Objective: To investigate the relative quality-of-life and disability burden in patients with uncompensated cervical, thoracolumbar, or cervical and thoracolumbar deformities. Summary of Background Data: The relative quality-of-life burden of cervical and thoracolumbar deformities have never been compared with each other. This may have significant implications when deciding on the appropriate treatment intervention for patients with combined thoracolumbar and cervical deformities. Methods: When defining CD C2–C7 sagittal vertical axis (SVA)>4 cm was used while a C7–S1 SVA>5 cm was used to defined thoracolumbar deformity. Patients with both SVA criteria were defined as "combined." Primary analysis compared patients in the different groups by demographic, comorbidity data, and quality-of-life scores [EuroQOL 5 dimensions questionnaire (EQ-5D)] using t tests. Secondary analysis matched deformity groups with propensity scores matching based on baseline EQ-5D scores. Differences in disease-specific metrics [the Oswestry Disability Index, Neck Disability Index, modified Japanese Orthopaedic Association questionnaire (mJOA)] were analyzed using analysis of variance tests and post hoc analysis. Results: In total, 212 patients were included in our analysis. Patients with CD only had less neurological deficits (mJOA: 14.6) and better EQ-5D (0.746) scores compared with patients with combined deformities (11.9, 0.716), all P <0.05. Regarding propensity score–matched deformity cohorts, 99 patients were matched with similar quality-of-life burden, 33 per deformity cohort. CD only patients had fewer comorbidities (1.03 vs. 2.12 vs. 2.70; P <0.001), whereas patients with combined deformity had more baseline neurological impairment compared with CD only patients (mJOA: 12.00 vs. 14.25; P =0.050). Conclusions: Combined deformity patients were associated with the lowest quality-of-life and highest disability. Furthermore, regarding deformity cohorts matched by similar baseline quality-of-life status (EQ-5D), patients with combined deformities were associated with significantly worse neurological impairments. This finding implies that quality of life may not be a direct reflection of a patient's disability status, especially in patients with combined cervical and thoracolumbar deformities. Level of Evidence: Level III.